If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(1-6x)-6x=6(x-7)+5
We move all terms to the left:
-7(1-6x)-6x-(6(x-7)+5)=0
We add all the numbers together, and all the variables
-7(-6x+1)-6x-(6(x-7)+5)=0
We add all the numbers together, and all the variables
-6x-7(-6x+1)-(6(x-7)+5)=0
We multiply parentheses
-6x+42x-(6(x-7)+5)-7=0
We calculate terms in parentheses: -(6(x-7)+5), so:We add all the numbers together, and all the variables
6(x-7)+5
We multiply parentheses
6x-42+5
We add all the numbers together, and all the variables
6x-37
Back to the equation:
-(6x-37)
36x-(6x-37)-7=0
We get rid of parentheses
36x-6x+37-7=0
We add all the numbers together, and all the variables
30x+30=0
We move all terms containing x to the left, all other terms to the right
30x=-30
x=-30/30
x=-1
| 6(v+6)-8v=20 | | y=y^2−3y | | 78.75+80.25x=40+90.75x | | (8h+2)^2-1515;h=3 | | a+20=37 | | 72=6(x+6) | | 90=1.8c+32 | | 7(p+8)+4=81 | | 32-8-12x=11(2x-6) | | 2t−–2=10 | | 4(x-7)-6x=-24 | | 10+7/45=x | | 7x-12=5x-1 | | 18+n=36 | | 9(n–4)=45 | | -4-14y=2(7y-16) | | x-(-7-4x)=8 | | y=372000(1.05)^6 | | -8w+4(w-5)=-28 | | y=-5+2.5 | | 2x1=0 | | 2(w)+2(w+12)=68 | | -5/4p-1/2=-3/4+5/8p | | -4(2x-9)+6(-x+1)=-8x-5(3x-3 | | k+18=5 | | -2(x-4)=20-2x+12x | | -0.5x=-2.75 | | 4x–7x+8x= | | 4x+35-15=9(x-5) | | 3-5x=-1-6x | | 22=4+6w | | 0.2(x+500)=3,750 |